1988
DOI: 10.1002/ajpa.1330770104
|View full text |Cite
|
Sign up to set email alerts
|

Changes in body proportions of Japanese medical students between 1961 and 1986

Abstract: Since 1945, the Japanese physique has changed a great deal. Physical examinations of medical students at Kyushu University have been carried out on an annual basis since 1939. We investigated changes in body proportions using data on 813 medical students examined from 1961 to 1986. During these 26 years, standing height has increased by 4.69 cm, arm length by 2.58 cm, and sitting height by 0.79 cm. Thus, the Japanese have grown taller and their extremities are longer, yet the trunk has not changed significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
22
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 5 publications
5
22
0
Order By: Relevance
“…Decreases in RSH per decade estimated in the present study are only about half those estimated for Japanese school-goers by Tanner et al (1982). Amounts of change estimated here are also less than those for fourth-year male medical students in Kyushu measured between 1961 and 1986 (Takamura et al, 1988). Estimates using Japanese school data over a longer period with birth cohorts from 1943 to 1978 (Ali et al, 2000) indicate amounts of change more similar to those reported in the present study, particularly for families in Taipei.…”
Section: Comparisons With Other Studiessupporting
confidence: 53%
See 2 more Smart Citations
“…Decreases in RSH per decade estimated in the present study are only about half those estimated for Japanese school-goers by Tanner et al (1982). Amounts of change estimated here are also less than those for fourth-year male medical students in Kyushu measured between 1961 and 1986 (Takamura et al, 1988). Estimates using Japanese school data over a longer period with birth cohorts from 1943 to 1978 (Ali et al, 2000) indicate amounts of change more similar to those reported in the present study, particularly for families in Taipei.…”
Section: Comparisons With Other Studiessupporting
confidence: 53%
“…In most studies, however, environmental change is not quantified. Qualitative evidence suggests, though, that the greatest relative increases in leg length tend to be reported in settings in which the greatest changes in developmental environments are likely (Bogin et al, 2001(Bogin et al, , 2002Ohyama et al, 1987;Takamura et al, 1988;Tanner et al, 1982). The inference that emerges from existing studies is that differences in outcome are not simply related to intrinsic differences between the sexes or between populations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of health and nutrition on crural indices have not been explicitly examined among living humans, though Auerbach (2007a) did not find covariation in changes in crural indices and subsistence over time in pre-Columbian North America. A few studies have indicated that significant increases occur in the relative length of the lower limbs relative to overall stature when modern human groups encounter an increase in nutrition and decrease in environmental stress (Tanner et al, 1982;Takamura et al, 1988;Bogin and Rios, 2003). However, the age and sex of individuals experiencing augmentations in health and diet has an effect on the observed impact on stature and relative lower limb length (Malina et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators expect that the relative leg length of Japanese will eventually reach that of the European population (Ohyama et al, 1987), but when the proportions of present-day Japanese are compared with those of the European population of the same height, the difference is still clear (Hoshi, 1984). Takamura et al (1988) studied the secular changes in relative arm length (A/H) and arm length relative to sitting height (A/S) during the 26 years between 1961-62 and 1985-86. They found that A/H did not change during this period, but A/S increased after 1971-72, especially in the tall group.…”
Section: Statistical Reports On Anthropometric Datamentioning
confidence: 99%